Battery insulation sheet, manufacturing method thereof and battery module comprising battery insulation sheet
The battery insulating sheet made by the lamination process uses the design of the aerogel layer to solve the problems of insufficient thermal insulation, durability and dust formation in the prior art, and achieve improved insulation performance and durability, while reducing the process cost.
Patent Information
- Application Number
- CN202410818717.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-16
- Filing Date
- 2024-06-24
- Publication Date
- 2025-02-21
AI Technical Summary
The existing battery insulating sheets have shortcomings in thermal insulation, durability and dust formation, especially in high temperatures, which are prone to breakage and difficult to process into small thicknesses and shapes.
The battery insulating sheet with a first substrate, an aerogel layer and a second substrate structure is fabricated by a lamination process, and the aerogel layer is designed to meet a specific compression density range and to form improved heat without the need for an adhesive Insulation, durability and compressibility.
Improved thermal insulation, durability and dust formation are achieved, reducing manufacturing process costs, and maintaining stability at high temperatures to reduce or prevent dust generation.
Smart Images

Figure CN119489596A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of priority from Korean Patent Application No. 10-2023-0106765 filed on August 16, 2023 in the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0003] Example embodiments relate to a battery insulating sheet, a method of manufacturing the battery insulating sheet, and a battery module including the battery insulating sheet. Background Art
[0004] A secondary battery is or includes a power storage system that converts electrical energy into chemical energy, stores chemical energy, and provides high energy density. Compared to primary batteries, which are usually non-rechargeable, secondary batteries are rechargeable and are commonly used in information technology (IT) devices (such as, for example, smart phones, mobile phones, laptops, tablet computers, etc.). People are very interested in electric vehicles to reduce or prevent environmental pollution, and high-capacity secondary batteries can be used in electric vehicles. Secondary batteries can exhibit characteristics (such as, for example, high density, high output, and stability).
[0005] When multiple high-capacity battery cells are included, such as in lithium-ion secondary batteries, one battery cell may overheat and may enter thermal runaway for various reasons, which may adversely affect other battery cells adjacent thereto. Therefore, it may be desirable to thermally isolate adjacent battery cells from each other.
[0006] Conventionally, a plate or an insulating resin sheet is disposed between the battery cells to isolate and insulate adjacent battery cells from each other. Summary of the invention
[0007] Example embodiments include a battery insulating sheet manufactured by a simple process and having improved, desired or advantageous thermal insulation, compressibility, durability, and dustiness, a method of manufacturing the battery insulating sheet, and a battery module including the battery insulating sheet.
[0008] Example embodiments include a battery insulating sheet having a structure in which a first substrate, an aerogel layer, and a second substrate are stacked (e.g., sequentially stacked), wherein each of the opposite surfaces of the aerogel layer directly faces the first substrate or the second substrate adjacent thereto. In examples, each of the opposite surfaces of the aerogel layer contacts the first substrate or the second substrate adjacent thereto.
[0009] A separate layer including an adhesive may not be provided between the aerogel layer and the first substrate or the second substrate. For example, a separate layer including an adhesive between the aerogel layer and the first substrate or the second substrate may be omitted.
[0010] The aerogel layer may satisfy the following formula 1.
[0011] [Formula 1]
[0012] 0.1≤PD1≤0.5, where PD1=PA / PB
[0013] In the above formula 1, PA indicates the mass per unit volume of the aerogel layer after a pressure of 0 kN (equivalent to no pressure) is vertically applied to the aerogel layer (g / cm 3 ), and PB indicates the mass per unit volume of the aerogel layer after a pressure of 5 kN is vertically applied to the aerogel layer (g / cm 3 ).
[0014] The aerogel layer may satisfy the following formula 2.
[0015] [Formula 2]
[0016] 0.1≤PD2≤0.4, PD2=PB / PC
[0017] In the above formula 2, PB indicates the mass per unit volume of the aerogel layer after a pressure of 5 kN is vertically applied to the aerogel layer (g / cm 3 ), and PC indicates the mass per unit volume of the aerogel layer after a pressure of 20 kN is vertically applied to the aerogel layer (g / cm 3 ).
[0018] Each or at least one of the first substrate and the second substrate may include a resin, a metal, an inorganic material other than a metal, or a composite thereof.
[0019] Each or at least one of the first substrate and the second substrate may have an air permeability of about 800 sec / 100 cc to 40,000 sec / 100 cc.
[0020] The aerogel layer may include at least one of a fiber support, an aerogel, and a functional material including a binder, a dispersant, or a combination thereof.
[0021] The fibrous support may be or include at least one of natural fibers, silica fibers, glass fibers, ceramic fibers, carbon fibers, graphite fibers, mineral fibers, and polymer fibers.
[0022] Aerogels can have a diameter of about 500 m 2 / g~1,000m 2 / g Brunauer, Emmet and Teller (BET) specific surface area.
[0023] The binder may include a water-based polymer binder.
[0024] The dispersant may be or include at least one of a surfactant and a phosphate salt.
[0025] The fiber support may be included at about 25 wt % to 60 wt %, the aerogel may be included at about 30 wt % to 70 wt %, and the binder may be included at about 0.1 wt % to 25 wt % based on the total amount of the aerogel layer.
[0026] Based on the total amount of the aerogel layer, the included fiber support may account for about 25wt% to 60wt%, the included aerogel may account for about 30wt% to 70wt%, the included binder may account for about 0.1wt% to 25wt%, and the included dispersant may account for about 0.1wt% to 5wt%.
[0027] Each or at least one of the first substrate and the second substrate may have a thickness of about 0.01 mm to 5 mm, and the aerogel layer may have a thickness of about 1 mm to 10 mm.
[0028] Another example embodiment includes a method of manufacturing a battery insulating sheet, the method including applying an aerogel composition to a first substrate, laminating a second substrate on the applied aerogel composition to manufacture a laminate, controlling a thickness of the laminate, and drying the laminate.
[0029] The aerogel composition can be produced by mixing a solvent with a functional material including a binder, a dispersant, or a combination thereof to produce a solvent mixture, mixing the solvent mixture with an aerogel powder to produce an aerogel mixture, and mixing the aerogel mixture with a fibrous support to produce the aerogel composition.
[0030] The solvent may be or include at least one of a polar solvent and a non-polar solvent.
[0031] When controlling the thickness of the laminate, the thickness of the laminate can be controlled by using roller pressing.
[0032] The laminate may be dried at a temperature of about 25°C to 100°C.
[0033] Yet another example embodiment includes a battery module including a plurality of battery cells and a battery insulation sheet provided between the plurality of battery cells, wherein first and second substrates of the battery insulation sheet are disposed to face battery cells adjacent thereto. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The attached drawings incorporated in this specification illustrate example embodiments and are used to further illustrate the technical concept of the present disclosure in conjunction with the detailed description of the following example embodiments, and the present disclosure is not to be construed as being limited to the contents shown in these drawings. In the drawings:
[0035] Figure 1is a schematic diagram showing the structure of a battery insulation sheet according to an example embodiment;
[0036] Figure 2 is a schematic diagram showing a battery insulation sheet according to an example embodiment formed between a plurality of battery cells; and
[0037] Figure 3 Schematic diagram showing the structure of a battery insulating sheet according to Comparative Example 1. DETAILED DESCRIPTION
[0038] Hereinafter, example embodiments will be described in detail so that those skilled in the art can easily implement the example embodiments. However, the embodiments may be implemented in many different forms and are not limited to the embodiments described herein.
[0039] When the term "about" or "substantially" is used in conjunction with a numerical value in this specification, it means that the relevant numerical value includes a tolerance of ±10% around the stated numerical value. When a range is specified, the range includes all values therebetween, such as an increment of 0.1%.
[0040] Insulation materials are materials that hinder or prevent the flow of heat from a higher temperature to a lower temperature and are used not only in refrigerators, cold rooms and buildings, but also in a variety of other industries including, for example, the aviation, electronics and automotive industries.
[0041] Insulating materials need to have improved, desired or advantageous thermal insulation through low thermal conductivity and mechanical strength, for example to maintain thermal insulation over time.
[0042] Aerogels are usually transparent or translucent advanced materials with nanoporous structures, showing very low density and low thermal conductivity. Therefore, aerogels have high potential as insulating materials and are considered to be highly efficient super-insulating materials that can be used in various industrial applications.
[0043] The attractive advantages of aerogels are that aerogels have lower thermal conductivity than conventional organic insulating materials (such as, for example, Styrofoam), and aerogels can address or help address key weaknesses of organic insulating materials (such as, for example, fire vulnerability and generation of hazardous gases upon fire).
[0044] However, in general, aerogels have been found to be very brittle, easily broken upon slight impact, and difficult to process into small thicknesses and shapes, which makes it challenging to manufacture insulating materials using only aerogels despite their improved, desirable, or advantageous thermal insulation.
[0045] A battery insulating sheet (insulating sheet) according to example embodiments may have a structure in which a first substrate, an aerogel layer, and a second substrate are sequentially stacked, wherein each of opposite surfaces of the aerogel layer may directly face the first substrate or the second substrate adjacent thereto.
[0046] The battery insulating sheet having the above structure may have improved, desired or advantageous thermal insulation, durability and compressibility, may have low manufacturing process cost, and may reduce or prevent dust generation from aerogel during the manufacturing process and actual use.
[0047] Figure 1 is a schematic diagram illustrating a structure of a battery insulation sheet according to an example embodiment.
[0048] refer to Figure 1 The battery insulating sheet 100 may be formed into a structure including a first substrate 110, an aerogel layer 120 formed on the first substrate 110, and a second substrate 130 formed on the aerogel layer 120, wherein the first substrate 110, the aerogel layer 120, and the second substrate 130 are stacked (eg, sequentially stacked).
[0049] A separate layer including an adhesive may not be provided between the aerogel layer 120 and the first substrate 110 or the second substrate 130. For example, a separate layer including an adhesive between the aerogel layer 120 and the first substrate 110 or the second substrate 130 may be omitted. The battery insulating sheet 100 may be manufactured by a single-step process under the conditions described below using the method described below, whereby the battery insulating sheet may be manufactured to have a structure in which the first substrate, the aerogel layer, and the second substrate are laminated (e.g., laminated in sequence) without an adhesive.
[0050] Various substrates (including, for example, but not limited to, resins, metals, inorganic materials other than metals, or composites thereof) may be used as each of the first substrate and the second substrate. The substrate may be in the form of, but not limited to, a film, a membrane, a sheet, or the like.
[0051] The resin may be or include, for example, at least one of polyethylene, polypropylene, polystyrene, polyethylene terephthalate, polyepoxy, and polyamide.
[0052] The metal may be or include, for example, at least one of copper, nickel, cobalt, iron, chromium, vanadium, palladium, ruthenium, rhodium, molybdenum, tungsten, iridium, silver, gold, and platinum. When a substrate made of or including any one or more of the above metals is used, the substrate may be subjected to an anti-corrosion treatment or an insulation treatment as required.
[0053] The inorganic material other than the metal may be or include at least one of calcium carbonate (CaCO 3 ), talc, and mica.
[0054] As an example, each or at least one of the first substrate and the second substrate may include an inorganic material other than metal, and as a specific example, each or at least one of the first substrate and the second substrate may include mica. In this case, thermal insulation, durability, etc. of the insulating sheet may be improved.
[0055] Each or at least one of the first substrate and the second substrate may include an inorganic material other than a metal having an air permeability of about 800 sec / 100cc to 40,000 sec / 100cc. For example, the air permeability may be adjusted depending on the thickness of the substrate and may be about 1,000 sec / 100cc to 30,000 sec / 100cc, about 1,000 sec / 100cc to 3,000 sec / 100cc, about 6,000 sec / 100cc to 10,000 sec / 100cc, about 10,000 sec / 100cc to 30,000 sec / 100cc, or about 20,000 sec / 100cc to 30,000 sec / 100cc. Air permeability is expressed as the time (in seconds) taken for 100cc of air to pass through an air permeability meter (Asahi Seiko OKEN air permeation tester, Model EGO1-55-1MR) when measured using a measurement method according to ISO 5635-5. By forming an aerogel layer between a first substrate and a second substrate (each or at least one of which includes an inorganic material other than a metal having an air permeability within the above range), in the absence of an adhesive layer, adhesion between each of the first substrate and the second substrate and the aerogel layer may be improved, which may be desirable or advantageous. When forming an adhesive layer, the adhesive component may not be heat-resistant, and thus the adhesive layer may be easily torn at a high temperature of about 200°C or more, but the battery insulating sheet according to the example embodiment may not include an adhesive layer and may have improved, desirable or advantageous stability at high temperatures.
[0056] The thickness of each or at least one of the first substrate and the second substrate may be about 0.01 mm to 5 mm, about 0.05 mm to 3 mm, or about 0.1 mm to 1 mm. By forming an aerogel layer between the first substrate and the second substrate having a thickness within any one of the above ranges, a battery insulation sheet having improved, desired, or advantageous thermal insulation, durability, and dust formation may be configured.
[0057] In example embodiments, the aerogel layer may satisfy Formula 1 below.
[0058] [Formula 1]
[0059] 0.1≤PD1≤0.5, PD1=PA / PB
[0060] In the above-mentioned Formula 1, PA indicates the mass per unit volume of the aerogel layer after a pressure of 0 kN or no pressure is vertically applied to the aerogel layer (g / cm 3 ), and PB indicates the mass per unit volume of the aerogel layer after a pressure of about 5 kN is vertically applied to the aerogel layer (g / cm 3 ). The value of PD1 may be, for example, about 0.1 to 0.5, about 0.1 to 0.4, or about 0.2 to 0.3. When the value of PD1 is within any of the above ranges, resistance to external impact or compression during installation of the battery module may be improved, which may be desirable or advantageous.
[0061] The aerogel layer may satisfy the following formula 2.
[0062] [Formula 2]
[0063] 0.1≤PD2≤0.4, PD2=PB / PC
[0064] In the above formula 2, PB indicates the mass per unit volume of the aerogel layer after a pressure of about 5 kN is vertically applied to the aerogel layer (g / cm 3 ), and PC indicates the mass per unit volume of the aerogel layer after a pressure of about 20 kN is vertically applied to the aerogel layer (g / cm 3 ). The value of PD2 may be, for example, about 0.1 to 0.4, about 0.15 to 0.35, or about 0.25 to 0.35. When the value of PD2 is within any of the above ranges, resistance to expansion inside the battery cell may be improved, which may be desirable or advantageous.
[0065] The values of PD1 and PD2 may indicate the compression density of the aerogel layer, from which the extent of the void region in the aerogel layer according to the applied pressure may be determined. According to the manufacturing method described below, the fiber support body that is substantially uniformly distributed and the aerogel present in a coating state on the surface of the fiber support body increase the void region in the aerogel layer, and thus the aerogel layer according to the example embodiment may have a value of PD1, a value of PD2, or values of PD1 and PD2 within the above range. By satisfying the value of PD1, the value of PD2, or the values of PD1 and PD2 as described above, the material may have improved, desired, or advantageous resistance to external impact or internal expansion, thermal insulation, and compressibility.
[0066] In example embodiments, the aerogel layer may include a fiber support, an aerogel, and a functional material including a binder, a dispersant, or a combination thereof.
[0067] The thickness of the aerogel layer may be about 1 mm to 10 mm, about 1 mm to 5 mm, or about 1 mm to 3 mm. By forming an aerogel layer having a thickness within any of the above ranges on a substrate, an insulating sheet having improved, desired, or advantageous thermal insulation and compressibility may be manufactured.
[0068] In example embodiments, a fiber support may be included in the aerogel layer to improve durability of the battery insulation sheet.
[0069] The fiber support may include fibers used as a support for common insulating materials. For example, the fiber support may be or include at least one of natural fibers, silica fibers, glass fibers, ceramic fibers, carbon fibers, graphite fibers, mineral fibers, and polymer fibers. As an example, the fiber support may include, but is not limited to, glass fibers. As an example, the glass fibers may include, but are not limited to, glass wool.
[0070] The natural fiber may be or include, for example, at least one of hemp, jute, flax, coir, kenaf, and cellulose.
[0071] The mineral fiber may be or include, for example, at least one of basalt, diatomaceous earth, alumina, silica, slag, and rock.
[0072] The polymer fiber may be or include, for example, at least one of nylon, polyimide, polyamide, polybenzimidazole, polybenzoxazole, polyamideimide, polyethylene terephthalate, polybutylene terephthalate, polyester, polyethylene (PE) and polypropylene (PP). As an example, the polymer fiber may include, but is not limited to, at least one of polyimide, polyamide and polybenzimidazole.
[0073] The fibrous support may be in the form of, for example, wool or chopped strands, but is not limited thereto.
[0074] The diameter of the fiber support can be, for example, about 0.1 μm to 20 μm, about 0.1 μm to 15 μm, about 0.1 μm to 5 μm, about 1 μm to 15 μm, or about 3 μm to 10 μm. By including a fiber support having a diameter within any one of the above ranges, the structure of the aerogel layer can be hardened and its manufacturing cost can be reduced.
[0075] The length of the fibrous support may be, for example, about 50 to 1000 μm, about 70 to 800 μm, or about 100 to 600 μm. By including a fibrous support having a length within any of the above ranges, the aerogel layer may be firmly formed, and durability may be improved.
[0076] The fiber support may be contained in an amount of about 5 wt% to 70 wt%, about 25 wt% to 60 wt%, or about 30 wt% to 50 wt% based on the total amount of the aerogel layer. The durability of the battery insulating sheet including the aerogel layer containing the fiber support within any of the above ranges may be improved.
[0077] In an example embodiment, the aerogel may have a diameter of about 500 m 2 / g~1,000m 2 / g BET specific surface area. For example, the aerogel may have a BET specific surface area of about 500 m 2 / g~950m 2 / g, about 550m 2 / g~950m 2 / g or about 600m 2 / g~900m 2 When the aerogel having a BET specific surface area value within any one of the above ranges is included, the insulating sheet may be able to effectively reduce or prevent heat transfer and heat propagation between a plurality of battery cells.
[0078] The average particle size D50 of the aerogel may be about 5 to 200 μm, about 10 to 100 μm, or about 20 to 50 μm. When the aerogel having an average particle size within any one of the above ranges is included, thermal insulation may be improved, thereby delaying heat transfer between a plurality of battery cells.
[0079] The content of the aerogel may be about 10 wt% to 90 wt%, about 30 wt% to 70 wt% or about 40 wt% to 60 wt% based on the total amount of the aerogel layer. When a battery insulating sheet including aerogel within any of the above ranges is manufactured, thermal insulation of the battery insulating sheet may be improved.
[0080] In example embodiments, the binder may include an aqueous polymer binder. For example, the aqueous polymer binder may be or include at least one of a water-based polymer, an anionic water-soluble polymer, a cationic water-soluble polymer, and a water-dispersible polymer.
[0081] The water-based polymer may be or include, for example, but is not limited to, at least one of polyvinyl alcohol, polyethylene oxide, polyacrylamide, and polyvinyl pyrrolidone.
[0082] The anionic water-soluble polymer may be or include a polymer having at least one functional group of carboxylic acid, sulfonic acid, sulfate, phosphate, and salts thereof. For example, the anionic water-soluble polymer may be or include a polymer having a carboxylic acid group, and may include, but is not limited to, polymaleic acid as an example.
[0083] The cationic water-soluble polymer may be or include a polymer having at least one functional group of: amine, ammonium, phosphonium, sulfonium and salts thereof. For example, the cationic water-soluble polymer may be or include a polymer having an amine group, and may be or include, but is not limited to, at least one of polyvinylamine and polyamine as an example.
[0084] The water-dispersible polymer may be or include, but is not limited to, at least one of a water-dispersible polyurethane and a water-dispersible polyester.
[0085] The binder may include a water-based polymer and a water-dispersible polymer. For example, the binder may include a water-based polymer having a bonding property and a dispersible property and a water-dispersible polymer having fire resistance. As an example, the binder may include polyvinyl alcohol and a water-dispersible polyurethane.
[0086] The weight ratio of the water-based polymer to the water-dispersible polymer may be about 1:1 to 1:5, about 1:1 to 1:4, or about 1:2 to 1:3. When the weight ratio of the water-based polymer to the water-dispersible polymer is within any one of the above ranges, in addition to the thermal insulation, dust formation, and compressibility of the insulation sheet, the fire resistance and mechanical properties of the insulation sheet may be further improved.
[0087] The content of the binder may be about 0.1 wt% to 25 wt%, about 0.5 wt% to 20 wt%, about 2 wt% to 15 wt%, or about 8 wt% to 15 wt%, based on the total amount of the aerogel layer. When a battery insulating sheet is manufactured using an aerogel composition including a binder within any one of the above ranges, the dusting property of the battery insulating sheet can be improved.
[0088] In example embodiments, the dispersant may be at least one of a surfactant and a phosphate salt. For example, the dispersant may include, but is not limited to, at least one of a nonionic surfactant, an anionic surfactant, an amphoteric surfactant, a natural surfactant (such as lecithin), and a phosphate ester.
[0089] When the dispersant is further included, the fibrous support and the aerogel may be present in the aerogel layer in a more uniformly dispersed state.
[0090] The content of the dispersant may be about 0.1 wt% to 6 wt%, about 0.1 wt% to 5 wt%, or about 0.1 wt% to 3 wt%, based on the total amount of the aerogel layer. When the dispersant is included within the above range, a battery insulation sheet having improved, desired or advantageous thermal insulation, compressibility, and dust formation can be manufactured.
[0091] The binder and the dispersant may be included in a weight ratio of about 1:0.001 to 1:0.67, about 1:0.001 to 1:0.5, or about 1:0.001 to 1:0.3. Mixing the binder and the dispersant in a weight ratio within any one of the above ranges may allow the aerogel to be more uniformly dispersed in the aerogel layer.
[0092] In example embodiments, the fibrous support may be included at about 5 wt % to 70 wt %, the aerogel may be included at about 10 wt % to 90 wt %, and the functional material may be included at about 0.5 wt % to 20 wt %, based on the total amount of the aerogel layer.
[0093] As an example, the fiber support may be included at about 25 wt % to 60 wt %, the aerogel may be included at about 30 wt % to 70 wt %, and the binder may be included at about 0.1 wt % to 25 wt % based on the total amount of the aerogel layer.
[0094] As an example, based on the total amount of the aerogel layer, the fiber support included may account for about 30 wt% to 50 wt%, the aerogel included may account for about 40 wt% to 60 wt%, and the binder included may account for about 8 wt% to 15 wt%. When the aerogel layer is formed within the above range, improved, desired or advantageous thermal insulation can be achieved while improving durability, and the bonding between the fiber support and the aerogel can be improved, thereby reducing or preventing dust generation.
[0095] As another example, based on the total amount of the aerogel layer, the included fiber support may account for approximately 25wt% to 60wt%, the included aerogel may account for approximately 30wt% to 70wt%, the included binder may account for approximately 0.1wt% to 25wt%, and the included dispersant may account for approximately 0.1wt% to 5wt%.
[0096] As an example, based on the total amount of the aerogel layer, the fiber support included may account for about 30 wt% to 50 wt%, the aerogel included may account for about 40 wt% to 60 wt%, the binder included may account for about 5 wt% to 10 wt%, and the dispersant included may account for about 0.1 wt% to 3 wt%. When the aerogel layer is formed within the above range, the dispersibility of the aerogel can be improved to achieve improved, desired or advantageous thermal insulation, while improving durability, and improving the bonding between the fiber support and the aerogel, thereby reducing or preventing dust generation.
[0097] In the aerogel layer, the surface of the fiber support may be coated with aerogel. In this case, the aerogel and the fiber support may be substantially uniformly distributed, and the bonding between the aerogel and the fiber support may be increased, which may reduce the generation of dust due to the shedding of the aerogel.
[0098] In example embodiments, the aerogel layer may be formed in a single layer structure or a multi-layer structure. When the aerogel layer is formed in a multi-layer structure, the aerogel layer may be formed to have about 2 to 10 layers, about 2 to 7 layers, or about 2 to 5 layers.
[0099] The method of manufacturing a battery insulating sheet according to an example embodiment may include applying an aerogel composition to a first substrate, laminating a second substrate on the applied aerogel composition to manufacture a laminate, controlling the thickness of the laminate, and drying the laminate. The method of manufacturing a battery insulating sheet may be performed by a single-step process (no separate lamination process of the substrate and the aerogel layer is required).
[0100] In the example method of manufacturing the battery insulation sheet, the detailed description of each of the first substrate and the second substrate may be similar or identical to the above description.
[0101] When applying the aerogel composition to the first substrate, the aerogel composition may be directly applied to the first substrate.
[0102] When the aerogel composition is applied to the first substrate, the first substrate may have a thin film structure having a long axis and a short axis, and the aerogel composition may be applied to the first substrate in the long axis direction or the short axis direction. As an example, the aerogel composition may be applied to the first substrate in the short axis direction. In this case, the internal pores may be controlled by reducing or preventing the formation of bubble droplets in the resulting aerogel layer.
[0103] An example method of making an aerogel composition may include mixing a solvent with a functional material including a binder, a dispersant, or a combination thereof to make a solvent mixture, mixing the solvent mixture with an aerogel powder to make an aerogel mixture, and mixing the aerogel mixture with a fibrous support to make an aerogel composition.
[0104] In example embodiments, when a solvent is mixed with a functional material to produce a solvent mixture, the solvent may be mixed with a binder, or the solvent may be mixed with a binder and a dispersant. A detailed description of each of the binder and the dispersant may be similar or identical to the above description.
[0105] In example embodiments, the solvent may be or include at least one of a polar solvent and a non-polar solvent.
[0106] The polar solvent may include water, an alcohol solvent, or a combination thereof.
[0107] The water may include, for example, purified water, deionized water, or a combination thereof.
[0108] The alcohol solvent may be or include, but is not limited to, at least one of methanol, ethanol, propanol, pentanol, butanol, hexanol, ethylene glycol, propylene glycol, diethylene glycol and glycerol.
[0109] The non-polar solvent may include a hydrocarbon solvent. For example, the hydrocarbon solvent may be or include at least one of hexane, pentane, heptane, toluene and benzene, and may be, but is not limited to, an alkane solvent (such as hexane) or a mixture including an alkane solvent.
[0110] The solvent may include water. Using water as a solvent can effectively reduce raw material costs and post-processing costs. When water is used as a solvent, water may not be fully mixed with the hydrophobic aerogel. In an example embodiment, the aerogel can be substantially uniformly dispersed by controlling the design of the mixing process, the mixing conditions, the addition of a binder and a dispersant, and the amount of the binder and the dispersant. This substantially uniform dispersion of the aerogel in the aerogel composition can form a battery insulating sheet with improved, desired or advantageous thermal insulation, durability, and dust formation of a small thickness without using a large amount of a binder.
[0111] The solvent may be included such that the weight ratio of the solvent to the total amount of solids in the aerogel composition is about 1:1 to 1:90. For example, the weight ratio of the solvent to the total amount of solids in the aerogel composition may be about 1:50 to 1:70, about 1:20 to 1:30, or about 1:2 to 1:10. By controlling the weight ratio of the solvent to the total amount of solids in the aerogel composition within any one of the above ranges, the viscosity may be controlled to form an aerogel layer by coating.
[0112] When the solvent mixture is mixed with the aerogel powder to produce the aerogel mixture, the detailed description of the aerogel powder may be similar or the same as described above.
[0113] When the aerogel mixture is mixed with a fibrous support to produce an aerogel composition, the detailed description of the fibrous support may be similar or the same as described above.
[0114] In each of the following, a mixer may be used for mixing: mixing a solvent with a functional material including a binder, a dispersant, or a combination thereof to produce a solvent mixture, mixing a solvent mixture with an aerogel powder to produce an aerogel mixture, and mixing an aerogel mixture with a fibrous support to produce an aerogel composition. For example, the mixer may include, but is not limited to, a planetary mixer and a Thinky mixer. TM mixer.
[0115] As an example, a planetary mixer can be used to mix the solvent mixture with the aerogel powder. Using a planetary mixer to mix the solvent mixture with the aerogel powder can result in the aerogel powder being substantially uniformly dispersed in the solvent.
[0116] A planetary mixer may be a device that can be used to mix or stir different substances to produce a substantially homogenous mixture. A planetary mixer may include blades that are capable of planetary motion.
[0117] In example embodiments, the planetary mixer may include at least one of one or more planetary blades and one or more high speed dispersing blades. As an example, the planetary mixer may include at least one planetary blade and at least one high speed dispersing blade.
[0118] Each or at least one of the planetary blades and the high-speed dispersion blades may be substantially continuously rotated about its axis. The rotational speed may be expressed in revolutions per minute (rpm).
[0119] In an example embodiment, the planetary mixer may include a first blade and a second blade having different rotation axes. For example, the first blade may be a low speed blade and the second blade may be a high speed blade. Low speed and high speed refer to the relative rotation speed between the first blade and the second blade. As an example, the first blade may be an open blade and the second blade may be a Despa TM blade.
[0120] The rotation speed of the first blade may be, for example, about 10 rpm to 100 rpm, about 10 rpm to 60 rpm, or about 30 rpm to 70 rpm. The rotation speed of the second blade may be, for example, about 100 rpm to 2000 rpm, about 100 rpm to 1000 rpm, about 300 rpm to 1700 rpm, or about 500 rpm to 1700 rpm.
[0121] When the functional material is added to the solvent and mixed with the solvent, the rotation speed of the first blade of the mixer may be about 10 rpm to 60 rpm, about 20 rpm to 50 rpm, or about 30 rpm to 40 rpm, and the rotation speed of the second blade may be about 300 rpm to 1700 rpm, about 600 rpm to 1000 rpm, or about 700 rpm to 800 rpm. As described above, when the solvent and the functional material are mixed with each other, a solvent mixture in which a binder, a dispersant, or a combination thereof is substantially uniformly dispersed can be produced to facilitate mixing of aerogels in subsequent processes.
[0122] When the solvent mixture and the aerogel powder are mixed with each other, the rotation speed of the first blade of the mixer may be about 30 rpm to 70 rpm, about 40 rpm to 70 rpm, or about 60 rpm to 70 rpm, and the rotation speed of the second blade may be about 500 rpm to 1700 rpm, about 600 rpm to 1600 rpm, or about 800 rpm to 1500 rpm. As described above, when the aerogel powder is added to the solvent mixture and mixed with the solvent mixture, the aerogel powder can be hindered or prevented from aggregating together to induce uniform dispersion.
[0123] When the aerogel mixture and the fiber support are mixed with each other, the rotation speed of the first blade of the mixer may be about 10rpm to 60rpm, about 20rpm to 50rpm, or about 30rpm to 40rpm, and the rotation speed of the second blade may be about 300rpm to 1700rpm, about 400rpm to 1500rpm, or about 800rpm to 1200rpm. Mixing the aerogel mixture with the fiber support as described above can remove air bubbles in the aerogel composition, control viscosity, and facilitate the dispersion of the fiber support in the uniformly dispersed aerogel, so that the aerogel surrounds the fiber support in the aerogel composition. A binder may be present between the aerogel and the fiber support to improve the bonding between the aerogel and the fiber support.
[0124] Applying the aerogel composition to the first substrate can be performed using common methods of applying a slurry to a substrate.
[0125] Applying the aerogel composition to the first substrate may be performed once or repeatedly performed two or more times.
[0126] In example embodiments, the aerogel composition may further include a silane compound. The silane compound may be or include, for example, at least one of 3-(trimethoxysilyl)propyl methacrylate, methyltriethoxysilane, methyltrimethoxysilane, ethyltrimethoxysilane, octadecyltrimethoxysilane, ethyltriethoxysilane, and 3-glycidoxypropyltrimethoxysilane. Further including a silane compound may further improve dispersibility.
[0127] In example embodiments, the aerogel composition may optionally further include additives (such as, for example, wetting agents, emulsifiers, compatibilizers, viscosity modifiers, pH modifiers, stabilizers, antioxidants, acid or base capture agents, metal deactivators, defoamers, antistatic agents, thickeners, adhesion promoters, coupling agents, flame retardants, impact modifiers, pigments, dyes, colorants, deodorants, etc.).
[0128] In example embodiments, the aerogel composition may be applied to a first substrate, and a second substrate may be laminated on the applied aerogel composition to form a structure in which the first substrate, the aerogel layer, and the second substrate are laminated (eg, sequentially laminated) without an adhesive.
[0129] In an example embodiment, when controlling the thickness of the laminate, the thickness of the laminate may be controlled by pressing using rollers. As an example, the laminate may be passed through gap rollers having a target gap thickness to control the thickness of the laminate.
[0130] In example embodiments, when drying the laminate, the drying may be performed at a temperature of, for example, about 25° C. to 100° C., about 45° C. to 90° C., or about 60° C. to 85° C. By drying the laminate within any one of the above temperature ranges, a solid aerogel layer may be formed on a substrate without adding a separate adhesive member or adhesive, while reducing or preventing separation between the substrate and the aerogel layer, and the coating may be formed in a shape in which the periphery of each of a plurality of dispersed fiber supports is coated with aerogel.
[0131] In example embodiments, pressing the laminate and drying the laminate may be performed separately, simultaneously, or at the same time.
[0132] By manufacturing a battery insulating sheet using the method according to the example embodiment, the battery insulating sheet can be easily manufactured without using a separate adhesive or forming an adhesive layer, and due to the uniform dispersion of the aerogel, the battery insulating sheet can have improved, desired or advantageous thermal insulation, durability and dust-forming properties even with a small thickness.
[0133] A battery module according to example embodiments may include a plurality of battery cells and a battery insulating sheet provided between the plurality of battery cells, wherein first and second substrates of the battery insulating sheet may face battery cells adjacent thereto.
[0134] Figure 2 is a schematic diagram illustrating a battery insulation sheet according to an example embodiment formed between a plurality of battery cells.
[0135] refer to Figure 2 , the battery insulating sheet 100 according to the example embodiment may be formed between a plurality of battery cells 200 included in a battery module. One surface of the battery insulating sheet 100 on which the first substrate is formed and another surface of the battery insulating sheet 100 on which the second substrate is formed may face the battery cell 200 adjacent thereto. When the battery insulating sheet 100 according to the example embodiment is formed between a plurality of battery cells 200, the resulting battery module can block a flame in one battery cell in advance, thereby substantially suppressing the flame from spreading to another battery cell 200 and spreading within a battery pack including the battery module at a higher safety level.
[0136] Hereinafter, examples are described. However, the following examples are intended only to illustrate or describe the present disclosure and should not be construed as limiting the present disclosure. Those skilled in the art can fully infer the details not described herein from a technical point of view, so their description will be omitted.
[0137] Manufacturing of battery insulation sheets
[0138] Example 1
[0139] 1. Manufacture of aerogel compositions
[0140] The mixture was prepared by adding polyvinyl alcohol (Sigma Aldrich) as a binder to deionized water as a solvent and stirring at 30 rpm using an open blade and Despa TM The blades were mixed at 700 rpm to produce a solvent mixture. Subsequently, the BET value was set at 800 m 2 / g of aerogel powder was added to the solvent mixture and the mixture was stirred at 70 rpm using an open blade and Despa TM The aerogel mixture was made by adding glass wool to the aerogel mixture and using an open blade at 30 rpm and using Despa TM The blades were mixed at 1200 rpm to produce an aerogel composition. A planetary mixer (DNTEK, PT-005) was used for mixing.
[0141] The solid content of the manufactured aerogel composition was found to be 50 wt% aerogel, 40 wt% glass wool and 10 wt% polyvinyl alcohol.
[0142] 2. Manufacturing of battery insulation sheets
[0143] The slurry of the manufactured aerogel composition was applied to a mica sheet (Pamica TM , Muscovite TM ), another 0.1 mm thick mica sheet was laminated thereon in a sandwich manner, and coating was performed while adjusting the thickness using a roller rolling method. Subsequently, an aerogel layer was formed by drying at 60° C. for 24 hours to manufacture a battery insulating sheet. It was found that the total thickness of the manufactured battery insulating sheet was 1.48 mm.
[0144] Example 2
[0145] A battery insulating sheet was manufactured using substantially the same method as in Example 1, except that an aerogel composition having a solid content of 60 wt % aerogel, 25 wt % glass wool and 15 wt % polyvinyl alcohol was manufactured by adjusting the input of raw materials when manufacturing the aerogel composition.
[0146] Example 3
[0147] A battery insulating sheet was manufactured using substantially the same method as in Example 1, except that an aerogel composition having a solid content of 65 wt % aerogel, 25 wt % glass wool and 10 wt % polyvinyl alcohol was manufactured by adjusting the input of raw materials when manufacturing the aerogel composition.
[0148] Example 4
[0149] A battery insulating sheet was manufactured using substantially the same method as in Example 1, except that an aerogel composition having a solid content of 45 wt % aerogel, 50 wt % glass wool and 5 wt % polyvinyl alcohol was manufactured by adjusting the input of raw materials when manufacturing the aerogel composition.
[0150] Example 5
[0151] A battery insulating sheet was manufactured using substantially the same method as in Example 1, except that an aerogel composition having a solid content of 50 wt % aerogel, 49.7 wt % glass wool and 0.3 wt % polyvinyl alcohol was manufactured by adjusting the input of raw materials when manufacturing the aerogel composition.
[0152] Example 6
[0153] A battery insulating sheet was manufactured using substantially the same method as in Example 1, except that an aerogel composition having a solid content of 40 wt % aerogel, 35 wt % glass wool and 25 wt % polyvinyl alcohol was manufactured by adjusting the input of raw materials when manufacturing the aerogel composition.
[0154] Example 7
[0155] A battery insulating sheet was manufactured using substantially the same method as in Example 1, except that water-dispersible polyurethane was used as a binder instead of polyvinyl alcohol when manufacturing the aerogel composition.
[0156] Example 8
[0157] 1. Manufacture of aerogel compositions
[0158] The mixture was prepared by adding polyvinyl alcohol (Sigma Aldrich) as a binder and a surfactant (Triton-X100, Sigma Aldrich) as a dispersant to deionized water as a solvent and stirring at 30 rpm using an open blade and Despa TM The blades were mixed at 700 rpm to produce a solvent mixture. Subsequently, the BET value was set at 800 m 2 / g of aerogel powder was added to the solvent mixture and the mixture was stirred at 70 rpm using an open blade and Despa TM The aerogel mixture was made by adding glass wool to the aerogel mixture and using an open blade at 30 rpm and using Despa TM The blades mixed the glass wool and aerogel mixture at 1200 rpm to produce the aerogel composition. A planetary mixer (DNTEK, PT-005) was used for mixing.
[0159] The solid content of the manufactured aerogel composition was found to be 50 wt% aerogel, 40 wt% glass wool, 9.9 wt% polyvinyl alcohol and 0.1 wt% dispersant.
[0160] 2. Manufacturing of battery insulation sheets
[0161] The slurry of the manufactured aerogel composition was applied to a mica sheet (Pamica TM , Muscovite TM ), another 0.1 mm thick mica sheet was laminated thereon in a sandwich manner, and coating was performed while adjusting the thickness using a roller rolling method. Subsequently, an aerogel layer was formed by drying at 60° C. for 24 hours to manufacture a battery insulating sheet. It was found that the total thickness of the manufactured battery insulating sheet was 1.48 mm.
[0162] Example 9
[0163] 1. Manufacture of aerogel compositions
[0164] The precipitate was prepared by adding polyvinyl alcohol (Sigma Aldrich) as a binder, water-dispersible polyurethane and a surfactant (Triton-X100, Sigma Aldrich) as a dispersant to deionized water as a solvent and stirring at 30 rpm using an open blade and Despa TM The blades were mixed at 700 rpm to produce a solvent mixture. Subsequently, the BET value was set at 800 m 2 / g of aerogel powder was added to the solvent mixture and the mixture was stirred at 70 rpm using an open blade and Despa TM The aerogel mixture was made by adding glass wool to the aerogel mixture and using an open blade at 30 rpm and using Despa TM The blades were mixed at 1200 rpm to produce an aerogel composition. A planetary mixer (DNTEK, PT-005) was used for mixing.
[0165] The solid content of the manufactured aerogel composition was found to be 50 wt% of aerogel, 40 wt% of glass wool, 3 wt% of polyvinyl alcohol, 6.9 wt% of water-dispersible polyurethane, and 0.1 wt% of dispersant.
[0166] 2. Manufacturing of battery insulation sheets
[0167] The slurry of the manufactured aerogel composition was applied to a mica sheet (PamicaTM , Muscovite TM ), another 0.1 mm thick mica sheet was laminated thereon in a sandwich manner, and coating was performed while adjusting the thickness using a roller rolling method. Subsequently, an aerogel layer was formed by drying at 60° C. for 24 hours to manufacture a battery insulating sheet. It was found that the total thickness of the manufactured battery insulating sheet was 1.48 mm.
[0168] Comparative Example 1
[0169] Manufacturing with Figure 3 The battery insulating sheet of the structure shown in FIG. Figure 3 Schematic diagram showing the structure of the battery insulating sheet according to this comparative example 1. A 1.2 mm thick insulating layer 121 (i.e., aerogel layer) is prepared. The insulating layer 121 is formed by impregnating glass wool felt with an aerogel precursor at low temperature and reduced pressure, gelling the resulting aerogel precursor and supercritically drying. The composition of the insulating layer 121 is 45 wt% aerogel, 45 wt% glass wool and 10 wt% binder. The insulating layer 121 thus manufactured is not self-adhesive and requires a bonding process in order to be laminated to the substrate. Therefore, a 0.05 mm adhesive layer 141 is formed on each of the upper and lower surfaces of the insulating layer 121 using lamination, hot melt or double-sided tape, and a 0.1 mm thick mica sheet is attached to the acceptable adhesive layer 141 to serve as the first substrate 111 and the second substrate 131, respectively. The total thickness of the insulating layer 121, the adhesive layer 141, the first substrate 111 and the second substrate 131 is 1.5 mm.
[0170] Experimental example
[0171] Experimental Example 1: Evaluation of Thermal Insulation
[0172] The thermal insulation of each of the insulating sheets manufactured in Examples 1 to 9 and Comparative Example 1 was evaluated.
[0173] Each insulating sheet was placed between a pair of opposing 1 mm thick aluminum plates and placed on a hot press. The upper plate of the hot press was heated to 350°C, and the lower plate of the hot press was not heated and maintained at an initial temperature of 40°C. Subsequently, a pressure of 20 kN was applied to the lower plate of the hot press, and the maximum temperature of the lower plate of the hot press within 11 minutes was measured. The results are shown in Table 1 below.
[0174] Experimental Example 2: Evaluation of compressibility
[0175] The compressibility of each of the insulating sheets manufactured in Examples 1 to 9 and Comparative Example 1 was evaluated.
[0176] After adjusting the zero point, each insulating sheet was inserted between aluminum plates (each having a thickness of 1 mm), and the thickness of the insulating sheet was measured using a universal testing machine (UTM) at a compression speed of 0.02 mm / sec from 0 kN applied load. Subsequently, the thickness of the insulating sheet under 5 kN and the thickness of the insulating sheet under 40 kN were measured, and the thickness reduction rate was expressed as the compression rate. The thickness reduction rate was calculated by thickness reduction rate = (thickness of the insulating sheet under 5 kN - thickness of the insulating sheet under 40 kN) / thickness of the insulating sheet under 5 kN × 100. The results are shown in Table 1 below.
[0177] Experimental Example 3: Evaluation of Dust Generation
[0178] The dust generation property of each of the insulating sheets manufactured in Examples 1 to 9 and Comparative Example 1 was evaluated.
[0179] Each insulating sheet was weighed before evaluation. Subsequently, the insulating sheet was placed on a rubber plate and tapped at five points (including the vertex and the center) of the insulating sheet with a rubber hammer at a constant rate, dusted and weighed. Subsequently, the weight reduction rate was calculated by (weight before physical impact - weight after physical impact) / weight before physical impact, and the results are shown in Table 1 below.
[0180] Experimental Example 4: Evaluation of compression density
[0181] The compression density of the aerogel layer of each of the insulating sheets produced in Examples 1 to 9 and Comparative Example 1 was evaluated.
[0182] The mass per unit volume of each aerogel layer was measured (g / mm). Using the same method as the compressibility evaluation method, the mass per unit volume (g / mm) was calculated using the mass, thickness, and area of the aerogel layer after vertically applying 0 kN (or no pressure), 5 kN, and 20 kN of pressure to the aerogel layer using UTM. 3 ), and by substituting the measured mass per unit volume of the aerogel layer before and after compression into the above formula 1 and formula 2, respectively, the values of PD1 and PD2 are derived. The results are shown in the following Table 1.
[0183] [Table 1]
[0184]
[0185] Referring to Table 1 above, in the case of Examples 1 to 9, thermal insulation, dust formation and compressibility are substantially all improved, and substantially all are desirable or advantageous. Referring to Examples 1 to 4, thermal insulation and dust formation vary depending on the content of the components of the aerogel composition. Compared with Examples 1 to 4, in the case of Example 5, due to the change in the content of the components of the aerogel composition, dust formation and compressibility are slightly reduced, but thermal insulation is maintained; in the case of Example 6, thermal insulation and compressibility are slightly reduced; in the case of Example 7, because the binder with fire resistance generally cannot act as a dispersant, dust formation is slightly reduced, but thermal insulation is maintained; in Example 8 in which the binder and the dispersant are mixed, thermal insulation, dust formation and compressibility are improved; in Example 9 in which polyvinyl alcohol and a water-dispersible polyurethane binder are mixed, thermal insulation, dust formation and compressibility are further improved. In Examples 1 to 9, the value of PD1 is in the range of 0.1 to 0.5, which shows improved, desired or favorable resistance to external impact or compression, and the value of PD2 is in the range of 0.1 to 0.4, which shows improved, desired or favorable resistance to expansion inside the battery cell.
[0186] In the case of Comparative Example 1, dust generation and expansion resistance are reduced when compared with other embodiments. When the insulating sheet is manufactured as in Comparative Example 1, an additional bonding process is required to bond the insulating sheet using the adhesive 141. Figure 3 The insulating layer 121 explained in the embodiment and the mica sheets as the first substrate 111 and the second substrate 131 are bonded to each other, which increases the process cost, and the aerogel is embedded in the surface of the glass wool felt while having a large particle size, whereby the aerogel can be easily detached from the glass wool felt, and thus a large amount of dust can be generated. In the case of Comparative Example 1, the input of the aerogel according to this method is limited, and quantitative input of the aerogel can be challenging.
[0187] Therefore, when using the aerogel composition according to example embodiments, thermal insulation, compressibility, and dust formation are improved, which is desirable or advantageous.
[0188] As is apparent from the above description, the battery insulating sheet according to the example embodiments may have improved, desired, or advantageous thermal insulation and durability, may have improved, desired, or advantageous thermal insulation and compressibility due to including an aerogel layer in which the aerogel is present in a coating state, may have a low manufacturing process cost, and may reduce or prevent the generation of dust from the aerogel during the manufacturing process and actual use.
[0189] Although the foregoing describes example embodiments, the present disclosure is not limited thereto, and it is contemplated that various modifications may be made within the scope of the claims, detailed description of example embodiments, and the accompanying drawings, and that these modifications also fall within the scope of the present disclosure.
Claims
1. A battery insulating sheet, comprising: a first substrate; Aerogel layer; as well as The second substrate; wherein: The first substrate, the aerogel layer and the second substrate are stacked in sequence; and Each of the opposing surfaces of the aerogel layer contacts the first substrate or the second substrate adjacent to the surface. 2 . The battery insulating sheet according to claim 1 , wherein a separate layer including an adhesive is not provided between the aerogel layer and the first substrate or the second substrate.
3. The battery insulation sheet according to claim 1, wherein the aerogel layer satisfies: 0.1≤PD1≤0.5, PD1=PA / PB; wherein PA indicates the mass per unit volume of the aerogel layer after a pressure of 0 kN is vertically applied to the aerogel layer, and PB indicates the mass per unit volume of the aerogel layer after a pressure of 5 kN is vertically applied to the aerogel layer.
4. The battery insulation sheet according to claim 1, wherein the aerogel layer satisfies: 0.1≤PD2≤0.4, PD2=PB / PC; wherein PB indicates the mass per unit volume of the aerogel layer after a pressure of 5 kN is vertically applied to the aerogel layer, and PC indicates the mass per unit volume of the aerogel layer after a pressure of 20 kN is vertically applied to the aerogel layer. 5 . The battery insulation sheet according to claim 1 , wherein at least one of the first substrate and the second substrate includes at least one of a resin, a metal, and an inorganic material other than the metal. 6 . The battery insulating sheet according to claim 1 , wherein at least one of the first substrate and the second substrate comprises an inorganic material other than the metal having an air permeability of 800 sec / 100 cc to 40,000 sec / 100 cc. 7 . The battery insulation sheet according to claim 1 , wherein the aerogel layer comprises at least one of a fiber support, an aerogel, and a functional material including a binder, a dispersant, or a combination thereof.
8. The battery insulating sheet according to claim 7, wherein the fiber support comprises at least one of natural fiber, silica fiber, glass fiber, ceramic fiber, carbon fiber, graphite fiber, mineral fiber and polymer fiber.
9. The battery insulating sheet according to claim 7, wherein the aerogel has a thickness of 500 m 2 / g~1,000m 2 / g BET specific surface area.
10. The battery insulating sheet according to claim 7, wherein the binder comprises an aqueous polymer binder.
11. The battery insulating sheet according to claim 7, wherein the dispersant is at least one of a surfactant and a phosphate-based salt.
12. The battery insulating sheet according to claim 7, wherein based on the total amount of the aerogel layer, the fiber support comprises 25 wt% to 60 wt%, the aerogel comprises 30 wt% to 70 wt%, and the binder comprises 0.1 wt% to 25 wt%.
13. The battery insulating sheet according to claim 7, wherein based on the total amount of the aerogel layer, the fiber support comprises 25wt% to 60wt%, the aerogel comprises 30wt% to 70wt%, the binder comprises 0.1wt% to 25wt%, and the dispersant comprises 0.1wt% to 5wt%.
14. The battery insulation sheet according to claim 1, wherein: At least one of the first substrate and the second substrate has a thickness of 0.01 mm to 5 mm; and The aerogel layer has a thickness of 1 mm to 10 mm.
15. A method for manufacturing a battery insulating sheet, the method comprising: applying the aerogel composition to a first substrate; laminating a second substrate on the applied aerogel composition to produce a laminate; controlling the thickness of the laminate; as well as The laminate was dried.
16. The method of claim 15, wherein the aerogel composition is produced by: mixing a solvent with a functional material comprising a binder, a dispersant, or a combination thereof to produce a solvent mixture; mixing the solvent mixture with an aerogel powder to produce an aerogel mixture; and The aerogel mixture is mixed with a fibrous support to produce the aerogel composition.
17. The method of claim 16, wherein the solvent comprises at least one of a polar solvent and a non-polar solvent.
18. The method of claim 15, wherein controlling the thickness of the laminate comprises controlling the thickness of the laminate by using roller pressing.
19. The method of claim 15, wherein the laminate is dried at a temperature of 25°C to 100°C.
20. A battery module, comprising: Multiple battery cells; as well as The battery insulating sheet according to any one of claims 1 to 14 or the battery insulating sheet manufactured by the method according to any one of claims 15 to 19, between the plurality of battery cells, wherein The first substrate and the second substrate of the battery insulation sheet are disposed to face battery cells adjacent to the first substrate and the second substrate, respectively.
Citation Information
Patent Citations
Spindle clamp device for machine tools that can control the angle division of the spindle
KR1020230106765A